2003
DOI: 10.1109/tasc.2003.813711
|View full text |Cite
|
Sign up to set email alerts
|

HTS hairpin microstrip filter on r-cut sapphire substrate

Abstract: We have developed a 17-pole high-temperature superconductor thin-film hairpin microstrip filter on r-cut sapphire substrate. We determined the optimum orientation of hairpin resonators on r-cut sapphire substrates, considering the anisotropy of dielectric permittivity. With optimum orientation, the desired frequency response was realized. On the other hand, when the orientation was not the optimum, the frequency response was violently disturbed. The cause of the disturbance of the frequency response was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This process achieved good epitaxial growth of YBCO and results in high-quality films to minimize surface resistivity. The selected substrate thickness and filter layout ensures a wide safety margin between the simulated current density and critical current density of the YBCO, such that the device could reliantly handle a 1 Watt RFI signal with 50 Ω microstrip transmission lines when cooled to 20 K. R-plane sapphire provides low-dielectric losses and high thermal conductivity, but requires accurate electromagnetic (EM) simulation to address its anisotropic permitivity [20]. The 3D EM model incorporates this anisotropic permittivity matrix and is simulated through Ansys HFSS.…”
Section: A Materialsmentioning
confidence: 99%
“…This process achieved good epitaxial growth of YBCO and results in high-quality films to minimize surface resistivity. The selected substrate thickness and filter layout ensures a wide safety margin between the simulated current density and critical current density of the YBCO, such that the device could reliantly handle a 1 Watt RFI signal with 50 Ω microstrip transmission lines when cooled to 20 K. R-plane sapphire provides low-dielectric losses and high thermal conductivity, but requires accurate electromagnetic (EM) simulation to address its anisotropic permitivity [20]. The 3D EM model incorporates this anisotropic permittivity matrix and is simulated through Ansys HFSS.…”
Section: A Materialsmentioning
confidence: 99%
“…Aiga et al [2] reported that the performance of HTS hairpin microstrip filters on R-Al 2 O 3 substrates had been influenced by the orientation of hairpin resonators, and thus it was difficult to design microwave circuits. On the other hand, A-plane Al 2 O 3 ( [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The HTS filters have been attractive for mobile communications applications [1][2][3][4][5][6][7][8][9] since the rapidly increasing demand for mobile communications puts challenges on both technology and system to conserve valuable frequency spectrum and enhance the performance. The system benefits from the HTS filters are mainly due to their high selectivity and low insertion loss.…”
Section: Introductionmentioning
confidence: 99%
“…More attractively, as compared with MgO and lanthanum aluminate substrates, sapphire substrate can be made to a larger size at a lower cost. Therefore, there is increasing interest in using sapphire substrate for fabrication of the HTS filters [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%